Effect of Electrolyte pH Level on the Surface Uniformity of Zinc Electroplating Coatings on AISI 1020 and 1070 Steels - Bimo Tauhid Ibrahim Ibrahim; Sulis Yulianto; Windarta; Nurul Hidayati Fithriyah; Budiyanto (Jurnal Konversi Energi dan Manufaktur, 2026)
Metal is one of the most frequently found materials in daily life and carbon steel is the most repeatedly used one. Carbon steel is a material that has the main elements in the form of iron and carbon, as well as supporting elements in the form of silicon, phosphorus, sulfur, and manganese. This study will compare the performance of zinc coating on high carbon steel (AISI 1070) and low carbon steel (AISI 1020), which research variables are electrolyte pH and coating quality testing with the corrosion rate method. It concluded that the reduction in the mass of the control specimen (which was not coated with Zn) was 2.83 g for AISI 1070 and for AISI 1020 was 2.69 g. The pH level in the electrolyte did not have a significant effect on the coating process, as evidenced by the Gr1P1S1 specimen (20 minutes, 40°C, pH 4) having an average thickness of 42.8 µm and Gr2P2S1 (20 minutes, 40°C, pH 3) having an average thickness of 43 µm. The electrolyte temperature and process time had a significant effect on the process. The lower the carbon content in carbon steel as a workpiece, the more difficult it would be to accept atoms from the anode/coating metal, as evidenced by the average increase in the mass of high carbon specimens of 0.70556 g compared to low carbon of 0.85333 g. In the test results using the average corrosion rate method, AISI 1070 showed a greater reduction in mass with an average figure of -0.1933 g compared to AISI 1020 at -0.098 g.